Vocabulary Repetition Following Multisensory Instruction Is Ineffective on L2 Sentence Comprehension: Evidence From the N400 - Pishghadam, Reza; Jajarmi, Haniyeh; Shayesteh, Shaghayegh; Khodaverdi, Azin; Nassaji, Hossein (Frontiers in Psychology, 2022)
Putting the principles of multisensory teaching into practice, this study investigated the effect ‎of audio-visual vocabulary repetition on L2 sentence comprehension. Forty participants were ‎randomly assigned to experimental and control groups. A sensory-based model of instruction ‎‎(i.e., emotioncy) was used to teach a list of unfamiliar vocabularies to the two groups. ‎Following the instruction, the experimental group repeated the instructed words twice, while ‎the control group received no vocabulary repetition. Afterward, their electrophysiological ‎neural activities were recorded through electroencephalography while doing a sentence ‎acceptability judgment task with 216 sentences under acceptable (correct) and unacceptable ‎‎(pragmatically violated) conditions. A one-way analysis of variance (ANOVA), a multivariate ‎analysis of variance (MANOVA), and a Bayesian repeated-measures ANOVA were used to ‎compare the behavioral and neurocognitive responses (N400 as the main language-related ERP ‎effect) of the two groups. The results showed no significant N400 amplitude difference in ‎favor of any of the groups. The findings corroborated the ineffectiveness of two repetitions ‎preceded by multisensory instruction on L2 sentence comprehension. ‎